2020
DOI: 10.1111/jfbc.13532
|View full text |Cite
|
Sign up to set email alerts
|

Kimchi markedly induces apoptosis in HT‐29 human colon carcinoma cells

Abstract: Kimchi, a traditional Korean fermented food, is mainly prepared with Baechu cabbages and radish, along with other sub-ingredients, such as red pepper powder, green onion, garlic, ginger, etc. (Park & Ju, 2018). The kimchi fermentation process consists of an initial stage, immature stage, optimally ripened stage, and over-ripened stage (Codex Alimentarius Commission, 2001). Kimchi fermented at 5°C for 3 weeks was shown to have improved fermented characteristics (such as pH and acidity), taste, and functionality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…RNA was isolated from colon tissue of each group using TRIzol reagent (Invitrogen Co., Carlsbad, CA, USA), and a NanoDrop ND-1000 (NanoDrop Technologies Inc., Wilmington, DE, USA) was used to quantify the isolated RNA. Afterwards, the quanti ed RNA was reverse transcribed using Superscript II reverse transcriptase (Invitrogen Co.), synthesized into cDNA, and used in experiments [21]. This cDNA was mixed with related primers (Bioneer, Daejeon, Korea) and SYBR green (Solis BioDyne, Tartu, Estonia), and gene expression was analyzed using a thermal cycler Bio-Rad CFX-96 real time system (Bio-Rad, Hercules, CA, USA) [22].…”
Section: Rt-qpcr Analysismentioning
confidence: 99%
“…RNA was isolated from colon tissue of each group using TRIzol reagent (Invitrogen Co., Carlsbad, CA, USA), and a NanoDrop ND-1000 (NanoDrop Technologies Inc., Wilmington, DE, USA) was used to quantify the isolated RNA. Afterwards, the quanti ed RNA was reverse transcribed using Superscript II reverse transcriptase (Invitrogen Co.), synthesized into cDNA, and used in experiments [21]. This cDNA was mixed with related primers (Bioneer, Daejeon, Korea) and SYBR green (Solis BioDyne, Tartu, Estonia), and gene expression was analyzed using a thermal cycler Bio-Rad CFX-96 real time system (Bio-Rad, Hercules, CA, USA) [22].…”
Section: Rt-qpcr Analysismentioning
confidence: 99%
“…The optical density (OD) value of each well was measured at 490 nm, and the inhibition rate of cell proliferation was calculated. The proliferation inhibition rate (%) = (OD control well -OD sample well )/OD control well × 100 [14].…”
Section: Detection Of Cell Proliferationmentioning
confidence: 99%
“…Depending on whether the ingredients are added or whether they are organic or non-organic, the taste, flavor, and textural and functional properties, such as anticancer and anti-inflammatory effects, may change [3]. In particular, in the study of Yu et al [4], when only organic cabbage was used, the proliferation of HT-29 cells was significantly inhibited through the activation of apoptosis, and the addition of sub-ingredients confirmed that the apoptosis effect improved.…”
Section: Introductionmentioning
confidence: 99%